ثبات محاور الأسنان في المستوى السهمي بعد المعالجة التقويمية - خليل فادي (Latakia University Journal -Medical Sciences Series, 2019)
تعدّ العضلات موجهاً لنمو القنزعة السنخية، ويُعدّ التوازن الفيزيولوجي لميلان محاور الأسنان ضماناً لثبات المعالجة, ينجم هذا الميلان عن التوازن العضلي (منطقة التوازن), يهدف البحث إلى دراسة ثبات محاور الأسنان في المستوى السهمي بعد المعالجة التقويمية من أجل معرفة حدود هذه المعالجة. تكونت عينة البحث من 40 مريضاً (ذكور وإناث), تم القيام بفحص عضلي ووظيفي دقيق لكل مريض، كما تم القيام بـ3 صور جانبية للرأس (قبل المعالجة T1, بعد نهاية المعالجة مباشرة T2, وسنة واحدة تقريباً بعد المعالجة T3). تم قياس الزاوية بين الثنية العلوية مع مستوى فرانكفورتI/F , وزاوية الثنية السفلية مع مستوى الفك السفليi/M , أما بالنسبة للأرحاء فقد اعتمدت الزاوية α (المحور الطولي للرحى العلوية مع مستوى الإطباق الوظيفي)، والزاوية β (المحور الطولي للرحى الأولى السفلية مع مستوى الإطباق الوظيفي). والزاوية γ(بين المحور الطولي للرحى الأولى السفلية والمحور الطولي للرحى الأولى العلوية) من أجل ملاحظة التغيرات الحاصلة في محاور الأسنان. النتائج: تشير إلى أن العضلات هي المحدد الأساسي لوضعية ميلان الثنايا، وأن لمحاور الأرحاء نزعة للعودة إلى ميلها الفيزيولوجي بعد المعالجة. Muscles guide the growth of the alveolar process. The balance of the physiological inclination of teeth is a guaranty of treatment stability. This inclination is the result of the muscular balance (Neutral Zone). The aim of this research was to study the stability of teeth axes in the sagittal plane after orthodontic treatment to know the limits of orthodontic treatment. The sample consisted of 40 patients (males and females), a precise muscular and functional examination was done for every patient. Three cephalometric radiographs were also done for every patient (T1 before treatment, T2 after treatment, T3 after one year of treatment). The angle between the upper central incisor and Frankfort Plane and between the lower central incisor and mandibular plane were measured. For molars we measured, α angle: ( between the long axis of the upper first molar and functional occlusion plane), β angle: (between the long axis of the lower first molar and functional occlusion plane), γ angle: (between the long axis of the lower first molar and the long axis of the upper first molar), for determining the changes in teeth axis. Results showed that the muscles are the basic determiner of central incisors inclination, and there is a tendency of molars to return to their physiological inclination after treatment.